The Impact of Digital Marketing and Electronic Word of Mouth on Property Purchase Decisions: The Mediating Role of Purchase Intention at Grand Wisata Housing - Andrean, Kevin; Yahya, Adibah; Kustiwan, Susan (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to analyze the influence of Digital Marketing (X1) and Electronic Word of Mouth (X2) on Purchase Decisions (Y) with Purchase Intention (Z) as a mediating variable in the context of property sales at Grand Wisata housing. This research was conducted using a quantitative approach with data collected through a questionnaire and analyzed using SmartPLS. A total of seven hypotheses were tested to evaluate the direct and mediated effects of Digital Marketing and Electronic Word of Mouth on Purchase Decisions. The results showed that Digital Marketing (X1) and Electronic Word of Mouth (X2) have a significant positive effect on Purchase Intention (Z) and Purchase Decision (Y). Additionally, Purchase Intention (Z) plays a mediating role between both Digital Marketing and Electronic Word of Mouth and Purchase Decision. These findings suggest that Digital Marketing and Electronic Word of Mouth strategies can effectively enhance customer interest and purchasing decisions for property products. The study contributes to the marketing literature in the property sector and provides practical implications for property developers to optimize their digital marketing and eWOM strategies.